Existence and Uniqueness of Solution of Summation-Difference Equation of Finite Delay in Cone Metric Space - Done, G. C.; Bondar, K. L.; Chopade, P. U. (Communications in Mathematics and Applications, 2020)
In this research article, we study the existence and uniqueness of solution of Summation-Difference equation of finite delay with nonlocal condition in cone metric space. The result is obtained by using the some extensions of Banach's contraction principle in complete cone metric space and also provide example to demonstrate of main result.